2020
DOI: 10.1080/21645515.2019.1710409
|View full text |Cite
|
Sign up to set email alerts
|

BBIQ, a pure TLR7 agonist, is an effective influenza vaccine adjuvant

Abstract: Better adjuvants are needed for vaccines against seasonal influenza. TLR7 agonists are potent activators of innate immune responses and thereby may be promising adjuvants. Among the imidazoquinoline compounds, 1-benzyl-2-butyl-1H-imidazo[4,5-c]quinolin-4-amine (BBIQ) was reported to be a highly active TLR7 agonist but has remained relatively unexplored because of its commercial unavailability. Indeed, in silico molecular modeling studies predicted that BBIQ had a higher TLR7 docking score and binding free ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
(56 reference statements)
0
20
0
1
Order By: Relevance
“…The ipso-displacement of a chloro functionality with 4chlorobenzylamine (for compound 8a), 4-methoxybenzylamine (for compound 8b), and 4-hydroxybenzylamine (for compound 8c) was carried out as described previously. 37 The nitro reduction was achieved using 1% palladium on activated charcoal (10% Pd basis) using a rubber bladder filled with hydrogen gas. The volatilities were removed by passing the reaction mixture through a bed of Celite to obtain an intermediate amino derivative that without further purification was reacted with trimethylorthovalerate in toluene to furnish 1H-imidazo [4,5-c]quinoline derivatives (8a−8c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ipso-displacement of a chloro functionality with 4chlorobenzylamine (for compound 8a), 4-methoxybenzylamine (for compound 8b), and 4-hydroxybenzylamine (for compound 8c) was carried out as described previously. 37 The nitro reduction was achieved using 1% palladium on activated charcoal (10% Pd basis) using a rubber bladder filled with hydrogen gas. The volatilities were removed by passing the reaction mixture through a bed of Celite to obtain an intermediate amino derivative that without further purification was reacted with trimethylorthovalerate in toluene to furnish 1H-imidazo [4,5-c]quinoline derivatives (8a−8c).…”
Section: Resultsmentioning
confidence: 99%
“…30,34,35 Vesatolimod (4) with 30-fold selectivity for hTLR7 over hTLR8 was tested in clinical trials to treat chronic hepatitis B virus (HBV) infection. 36 BBIQ (5), a TLR7 selective agonist, has been explored as a vaccine adjuvant 37 and as an immuno-chemotherapeutic agent against Plasmodium berghei. 21 Most recently, a whole virion inactivated SARS-COV-2 vaccine (BBV152) adjuvanted with a TLR7 agonist adsorbed to an alum adjuvant has been approved in India.…”
Section: Introductionmentioning
confidence: 99%
“…These TLR7/8 ligands either bind to both TLR7/8 receptors or selectively interact with either one to initiate a signaling cascade. For example, imiquimod activates TLR7, whereas CL097 induces TLR7/8 mediated responses [90] . Small structural modifications in TLR7/8 agonists may result in variable TLR7/8 pathway specific responses and selective induction of IFNs and inflammatory mediators [91] .…”
Section: Tlr7/8 Agonists As Potential Therapeutics To Treat Coronaviral Infectionsmentioning
confidence: 99%
“…Administration of TLR3, TLR9, TLR7, or TLR7/8 agonists resulted in viral inhibition and improved mouse survival [ 27 ]. Recent publications have further demonstrated that the combinations of synthesized TLR4, TLR7, and TLR7/8 ligands were potent adjuvants for recombinant influenza HA vaccines in different animal models [ 28 , 29 , 30 , 31 ]. Significantly, the TLR4 and TLR7 ligands—such as MPL/R837, TRAC-478, and 1Z105/1V270—synergistically increased antigen-specific, long-lasting humoral immune responses, Th1 cell-mediated or Th1/Th2-balanced immunity, and protection against homologous, heterologous, and heterosubtypic viral challenges [ 6 , 28 , 30 ].…”
Section: Adjuvants In Immune Responsesmentioning
confidence: 99%